SURFAKTAN UNTUK BAHAN BAKAR SOLAR DAN BIODIESEL - Firda Dimawarnita; Erliza Hambali (Jurnal Teknologi Industri Pertanian, 2021)
The government has determined that Indonesia is gradually implementing biodiesel as a substitute for fossil fuels. In September 2018 the B20 rule was established, then B30, and by the end of 2020 it became B50. That means 20%, 30%, and 50% of fuel is biodiesel. Fatty acid methyl ester (FAME) known as biodiesel which is synthesized from palm oil produces a high yield, up to 95%. However, in practice mixing FAME and diesel oil still has obstacles such as FAME will separate from diesel and form a gel, this is due to the hygroscopic nature of FAME and higher density of FAME compared to diesel oil. The decline in the quality of biodiesel is also caused by changes in some chemical and physical characteristics during storage. To overcome these problems, an emulsifier or surfactant solution is needed to homogenize the mixture of diesel fuel and biodiesel. Surfactants in biodiesel not only function as emulsifiers but also provide other added values, such as reducing hydrocarbons, CO, CO2, and NOx in exhaust gas emissions when compared to without surfactants. Some literature suggests that 35% reduction in hydrocarbon emissions occurs when Jatropha methyl ester has been mixed with surfactant and nano carbon compared to Jatropha methyl ester alone. The use of nano additives also showed differences in the stability of biodiesel and surfactants, the addition of nano additives in the form of nano carbon and nano cerium increased the stability and homogeneity of biodiesel for longer. Thus, biodiesel can be stable for a certain period of time. This review will show the various types of emulsifiers used in fuel mixing and the time of stability formed.Keywords: biodiesel, emulsifer, homogenization, palm oil, diesel fuel